Análisis del concepto de co-creación en algunas startups constructoras de Bogotá (2015)
In this research project, the concept of co-creation was assessed in a sample of construction Startups Bogota, in order to explore the level of influence of different external actors in the internal decisionmaking. For it was designed and applied an instrument of data collection, which was applied to ten (10) companies, throwing a first related to an important closeness and customer contact with the sales staff (76.9%) results with managers (92%), and designers or architects (53.8%).